MATRILINY AND DOMESTIC MORPHOLOGY: A STUDY OF THE NAIR TARAWADS OF MALABAR - Balakrishna Menon. P (School of Architecture, McGill University, 1998)
Among the few matrilineal communities from around the world were the Nairs of the south-western coast, a1so known as the Malabar coast, of India. The system of matrilineal consanguinity and descent practiced by the Nairs was remarkable for its complex kinship organization and joint family set up, and the unique status - social and economic - it afforded to the wornen ofthe community. Among the critical features of this system were: the mode of tracing descent and kin-ties along the line of ancestress; the holistic and ritually-significant quasi-corporate body, called tarawad; the relative latitude extended to wornen in both marriage and termination of marriage; the "duolocal residence" and the "visiting husband" system; the complex system of rights ofownership, division and transmission of family landed property conferred upon fernale descendants; and the existence ofa number of descent groups, caHed tavazhis, headed by fernale descendants and forming sub-clans -- sometirnes as large as one hundred rnembers -- ail living together in a tarawad house. These factors were reflected in the spatial morphology of the traditional Naïr house, an assemblage of four blacks, called the nalukettu. The different structural identities of the tarawad institution; the comparative latitude and the bias of inheritance that women enjoyed; the codes of marriage, interaction and avoidance; and the observation of rituals, an integral part of the cosmology and temporal cycle of the system, ail fmd expression in the layout and spatial organization. On the whole, the geometry of the Nair nalulcettu was a graphic metaphor of the social and behavioral patterns of the Nair community overlaid on the Hindu way of life, as interpreted by the community. This study investigates how the morphology of the traditional Nair houses was influenced by the matrilineal system and the concomitant gender roles and kinship pattern.